2022
DOI: 10.1155/2022/3042131
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Grinding Parameters of Tool Steel by the Soft Computing Technique

Abstract: Grinding is one of the most complex and accurate machining processes, and the efficiency of the grinding wheel depends significantly on its surface properties. This work aims to propose an algorithmic manner that reduces the cost and time to conduct grinding of an optimized DIN 1.2080 tool steel (SPK) using a soft computing technique to obtain the best combination of input parameters including depth of cut (20, 40, 60  μ m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…These include the count of hidden layers, the number of nodes within each hidden layer, the selection of the activation function for the hidden layer, the training function type, learning rate, and the number of training epochs 50 . In accordance with previous research findings, it has been demonstrated that the feedforward backpropagation ANN model attains optimal performance when configured with a singular hidden layer, a sigmoid tangent function for said hidden layer (Equation 9), and a pure linear activation function (Equation 10) [42][43][44][45][46]51 . This configuration was adopted in the present study.…”
Section: Modeling and Optimizationsupporting
confidence: 89%
See 1 more Smart Citation
“…These include the count of hidden layers, the number of nodes within each hidden layer, the selection of the activation function for the hidden layer, the training function type, learning rate, and the number of training epochs 50 . In accordance with previous research findings, it has been demonstrated that the feedforward backpropagation ANN model attains optimal performance when configured with a singular hidden layer, a sigmoid tangent function for said hidden layer (Equation 9), and a pure linear activation function (Equation 10) [42][43][44][45][46]51 . This configuration was adopted in the present study.…”
Section: Modeling and Optimizationsupporting
confidence: 89%
“…Establishing a robust benchmark for the evaluation of model efficacy constitutes a pivotal facet within the ambit of research endeavors. Within this study, a novel function denoted by Equation (3), as outlined in a preceding investigation [42][43][44][45][46] , was employed to assess the performance of both the response surface methodology (RSM) and artificial neural network (ANN)-based models.…”
Section: Modeling and Optimizationmentioning
confidence: 99%
“…During the development of the network, the best combination of hyper parameters was selected based on the procedure used by Refs. 55 , 56 , 64 , 65 . Moreover, the MATLAB toolbox was used to implement such networks.…”
Section: Modelingmentioning
confidence: 99%
“…High corrosion resistance, formability, strength, and ease of maintenance provided by any type of steel have raised their popularity in several applications. 1 Among various types of steel, 316 L stainless steel has found extensive applications in food, nuclear, chemical, and petrochemical industries. 2 The powder form of 316 L stainless steel also has special features including high melting point, low thermal conductivity, low oxygen sensitivity, and high absorptivity, all of which make it a proper choice for additive manufacturing (AM) processes.…”
Section: Introductionmentioning
confidence: 99%
“…High corrosion resistance, formability, strength, and ease of maintenance provided by any type of steel have raised their popularity in several applications. 1 Among various types of steel, 316 L stainless steel has found extensive applications in food, nuclear, chemical, and petrochemical industries. 2…”
Section: Introductionmentioning
confidence: 99%